Получение модифицированных акрилонитрилом нефтеполимерных смол; Ползуновский вестник; № 4-1 - Бондалетова Л. И. Людмила Ивановна; Бондалетов В. Г. Владимир Григорьевич; Кустова Е. А.; Бондалетов О. В. Олег Владимирович; Сутягин В. М. Владимир Михайлович (2011, 2011)
Заглавие с экрана